2010
DOI: 10.1080/17450390903461253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy intake and cold exposure on kinetics of plasma phenylalanine, tyrosine and protein synthesis in sheep

Abstract: An isotope dilution method of [2H5]phenylalanine (Phe) and [2H2]tyrosine (Tyr) was used to determine the effects of metabolisable energy (ME) intake and cold exposure on plasma Phe and Tyr turnover rates in sheep. Whole body protein synthesis (WBPS) was calculated with the [2H5]Phe model. Eight adult sheep were assigned to two dietary treatments receiving the same amount of crude protein and either 515 or 828 kJ x kg BW(-0.75) x d(-1) of ME (Me-ME diet and Hi-ME diet, respectively) with a crossover design for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Miaron and Christopherson (1997) stated that acute cold exposure may exert relatively small effects on whole blood arterial amino acid concentrations in sheep. A previous report of Sano, Murakami, Sasaki, and Al-Mamun (2010) showed that plasma amino acid concentrations were little influenced (only leucine, valine and glutamine changed) by cold exposure in sheep, which agrees with our present observation.…”
Section: Plasma Nefa and Free Amino Acidssupporting
confidence: 94%
“…Miaron and Christopherson (1997) stated that acute cold exposure may exert relatively small effects on whole blood arterial amino acid concentrations in sheep. A previous report of Sano, Murakami, Sasaki, and Al-Mamun (2010) showed that plasma amino acid concentrations were little influenced (only leucine, valine and glutamine changed) by cold exposure in sheep, which agrees with our present observation.…”
Section: Plasma Nefa and Free Amino Acidssupporting
confidence: 94%
“…The current study demonstrated that GL feeding might have positive effects on plasma PheTR and WBPS in sheep. The values of PheTR, TyrTR and WBPS found by our present study were comparable with previous results (Fujita et al 2006;Sano et al 2010). Until recently, to the best of our knowledge, effects of feeding garlic constituents on amino acid kinetics and WBPS have not been investigated clearly either in humans or in animals, except our previous report (Kamruzzaman et al 2011).…”
Section: Discussionsupporting
confidence: 91%
“…; Sano et al . ). Until recently, to the best of our knowledge, effects of feeding garlic constituents on amino acid kinetics and WBPS have not been investigated clearly either in humans or in animals, except our previous report (Kamruzzaman et al .…”
Section: Discussionmentioning
confidence: 97%